Ergonomic Laparoscopic Surgical Repair of three large external herniae through just three optimally placed working ports – A Case report with Review of Literature - Nagula, Mounish Raj; Joshi, Abhijit (Eastern Journal of Medical Sciences, 2023)
Currently, hernia repair is the most frequent procedure performed by general surgeons. Like many other abdominal operations, the laparoscopy revolution has influenced the surgical repair of external herniae as well. Laparoscopic repair of groin and ventral hernia have become more and more popular over the years. Ventral herniae are mostly repaired trans-peritoneally while groin herniae can be repaired both trans- as well as extra-peritoneally. Herein, we describe the case of a 60-year old man who presented to us with large umbilical and large bilateral inguinal herniae. All the three large external herniae were repaired laparoscopically, through just 3 carefully selected trocar sites. The purpose of this paper is to highlight the importance of ergonomics in optimum laparoscopic trocar placement, so as to achieve maximum results with minimum number of port sites.